The Effect of Multiple Representation-Based Guided Inquiry on Learning Outcomes Reviewed from Scientific Thinking Skills - Rendy Priyasmika (EduChemia (Jurnal Kimia dan Pendidikan), 2021)
This research's background is the importance of understanding the concept of chemical equilibrium material to understand the complex chemical interactions. This material is seen as one of the most difficult subjects in learning chemistry at the school and university level, so it requires a good understanding of studying it. A good and appropriate understanding of learning chemistry requires scientific thinking skills. This study aimed to analyze the effect of guided inquiry learning models based on multiple representations on student learning outcomes in chemical equilibrium material. The design of this study used a Pre-Experimental Design with a One-Shot Case Study model. The subjects in this study were 25 students of the Chemistry Education program at Billfath University who took the Basic Chemistry course. The data was collected using the Classroom Test of Scientific Reasoning (CTSR) instrument and test questions on the learning outcomes of chemical equilibrium material. The data analysis technique in this study used a non-parametric statistical test with a t-test. The results showed (1) the learning outcomes of students with high scientific thinking skills were higher than students with low scientific thinking skills, (2) there was a significant effect of the guided inquiry learning model based on multiple representations on student learning outcomes.